Tolerance in Diversity of Colleges in Islamic Moderation Comprehension - Gamal Abdul Nasir Zakaria; Mulyana Abdullah; Ahmad Zaldi (Universitas Pendidikan Indonesia, 2023)
Islam teaches us to be fair and objective, even to the most we hate, and we should not hate the muslim groups obviously. These understanding, attitude and behavior need to be implanted substantially. Here the Islamic moderation principles need to be understood and internalized by every muslims in Indonesia, including the colleges to be having a tolerant in diversities. To assess the influence of Islamic moderation to the college’s tolerance, the research which designed with a quantitative approach applied the analysis technique of product moment correlation and took the muslim colleges of UPI as the subject. The results found that the muslim colleges knew and understood that Islam is actually true. But, their understanding has tendency based on Islamic meaning comprehension which is definitely (qath’i), meanwhile the teaching that is zanni has not widely knew. In addition, the attitude of tolerance towards diversity and differences among muslim colleges is quite high, especially the attitude of tolerance in inter-religious harmony. However, the less tolerant attitude towards differences of fellow Muslims who have different beliefs still found. Meanwhile, the results of hypothesis testing proves that there is a significant effect of the Islamic moderation comprehension toward the attitude of tolerance in diversity.